Recent trends in primary-care antidepressant prescribing to children and young people: an e-cohort study - Keith Lloyd (Psychological Medicine, 2016)
Concerns relating to increased use of psychotropic medication contrast with those of under-treatment and under-recognition of common mental disorders in children and young people (CYP) across developed countries. Little is known about the indications recorded for antidepressant prescribing in primary care in CYP.This was an electronic cohort study of routinely collected primary-care data from a population of 1.9 million, Wales, UK. Poisson regression was undertaken to model adjusted counts of recorded depression symptoms, diagnoses and antidepressant prescriptions. Associated indications were explored.3 58 383 registered patients aged 6-18 years between 1 January 2003 and 31 December 2013 provided a total of 19 20 338 person-years of follow-up. The adjusted incidence of antidepressant prescribing increased significantly [incidence rate ratio (IRR) for 2013 = 1.28], mainly in older adolescents. The majority of new antidepressant prescriptions were for citalopram. Recorded depression diagnoses showed a steady decline (IRR = 0.72) while depression symptoms (IRR = 2.41) increased. Just over half of new antidepressant prescriptions were associated with depression (diagnosis or symptoms). Other antidepressant prescribing, largely unlicensed, was associated with diagnoses such as anxiety and pain.Antidepressant prescribing is increasing in CYP while recorded depression diagnoses decline. Unlicensed citalopram prescribing occurs outside current guidelines, despite its known toxicity in overdose. Unlicensed antidepressant prescribing is associated with a wide range of diagnoses, and while accepted practice, is often not supported by safety and efficacy studies. New strategies to implement current guidance for the management of depression in CYP are required.